Exploring Traditional Wild Edible Plants – book review - Nurwahidah, Umi; Ahmad Reza Maulana; Oscar Njuru May (Ethnobotany Research and Applications, 2025)
A review of Exploring Traditional Wild Edible Plants. CRC Press, Taylor & Francis Group, LLC. Pp 357. £160.00 (eBook), ISBN 978-1-003-39593-5 (eBook). The book Exploring Traditional Wild Edible Plants explains the diverse roles wild edible plants (WEPS) play in nutrition, traditional medicine, and sustainable healthcare. It is divided into 14 interconnected chapters that present a comprehensive perspective, linking ethnobotanical origins with pharmacological benefits. This common theme helps people understand the essential nature of WEPs and prompts discussions about their benefits for nutrition, medicine, and the environment in various contexts.